Educating teacher for muallaf: the tawhidic base - Ab. Halim Tamuri (Penerbit Universiti Kebangsaan Malaysia, 2015)
The main aim of this paper is to discuss the role of tawhid in developing teacher education system for the muallaf. Basically, every teacher should have good akhlak, since they are generally regarded as the role models or exemplars for their students especially for the muallaf students. These teachers are the persons who directly educate the muallaf about Islam and guide them closely how live as good Muslim. Therefore, in Islam, tawhid is not limited to divine or metaphysical aspects, but it also should be regarded as the universal principle or rule that will guide all human activities in order to confirm to the will of Allah. This primary concept is related to the human being’s temporal duty in this universe as khalīfatullāh, and with his or her permanent duty as ‘abdullāh. As a result, education in Islam cannot be separated from the concept of tawhid. Thus, this concept of tawhid should be correctly understood by the teachers particularly in educating our new Muslim brothers and sisters.